Answer :

α2 + pα + 1 = 0, β2 + pβ + 1 = 0

α + β = -p, αβ = 1


γ2 + qγ + 1 = 0, δ2 + qδ + 1 = 0


δ – γ = , γδ = 1


(α – γ)(α + δ)(β – γ)(β + δ)


= (α2 + α(δ – γ) – γδ)(β2 + β(δ – γ) – δγ)










Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

–x2 + RD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the fRD Sharma - Mathematics

Solve:
<
RD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics